Model of Good Practices for Principal Communication in Improving the Quality of Education - Nurul Hasanah; M. Rusydah (Yayasan Salam Cerdas Al-Fattah, 2024)
This research aims to explore the communication of school principals through the implementation of effective communication in schools. This study uses a literature study method with a data triangulation approach, reviewing relevant literature on organizational communication theory, educational leadership, and previous research on the communication practice of school principals. Primary and secondary data were obtained from relevant previous research studies. The results of the study show that effective communication in schools can strengthen the relationship between principals, teachers, and students, as well as improve teacher motivation and performance. However, there are several challenges that hinder the implementation of effective communication, such as structural barriers, unequal opportunities for participation, and lack of transparency in decision-making. This study suggests the application of two-way communication that builds constructive feedback and increases participation